Persamaan Pola Intensitas Hujan Fungsi dari Durasi dan Probabilitas Hujan untuk Kawasan Daerah Aliran Sungai (DAS) Bagian Hulu (Kasus Das Cimanuk - Jawa Barat) - Rohmat, Dede; Soekarno, Indratmo (MEDIA KOMUNIKASI TEKNIK SIPIL, 2005)
The objective of this research is to find a rainfall intensity model in the form simple equation, but can be usage to predict rainfall intensity by both random rainfall duration and probability accurately.  The final equation of rainfall intensity of the modeling result, have the form It,p=f(t,p).  Prediction of rainfall intensity by both random rainfall duration (t; ours) and probability (p; %) can be conduct by an equation is that.  The general equation of rainfall intensity as function both of t and p, formulated by substitution all of quantitative (constant) values by   a1, a2, b1, b2 notations as constants.  At the all group of rainfall durations, the value of rainfall intensity of modeling result (It,p) with empirical (Ie) have a close value.  The correlations value about 0.98 until 0.99.  At the all group of times periods (T) of rainfall event, the value of It,p is valid.  The rainfall intensity of modeling results closely with empirical data and have a pattern as same as others method pattern.  By comparing with others method, correlations values It,p is best at T = 2; 3; 5; 7; and 15 years. At t > 4 ours, there is bigger deviation relatively between It,p than the calculation result of others method.  That is occurring, because at the t mentioned the value of It,p is an extrapolation result. To implement the equation on others region, have need of a similar research in others region.  That must be using the same of both base equation and technical analysis guidance.Keywords: Rainfall Equation, Rainfall Intensity, Rainfall Duration, Rainfall Probability, Upper WatershedPermalink: http://www.ejournal.undip.ac.id/index.php/mkts/article/view/3921[How to cite: Rohmat, D. dan Soekarno, I., 2005, Persamaan Pola Intensitas Hujan Fungsi dari Durasi dan Probabilitas Hujan untuk Kawasan Daerah Aliran Sungai (DAS) Bagian Hulu (Kasus Das Cimanuk - Jawa Barat), Jurnal Media Komunikasi Teknik Sipil, Volume 13, Nomor 3, pp. 48-66]